1996
DOI: 10.1021/jo951194h
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of 1-Alkoxy-1-glycosyl Radicals:  The Manno- and Rhamnopyranosyl Series. Inversion of α- to β-Pyranosides and the Fragmentation of Anomeric Radicals

Abstract: The formation and stereoselective quenching of 1-mannopyranosyl radicals by a tributyltin hydride-mediated intramolecular 1,5-hydrogen abstraction sequence is described. A competing process is 1,4-hydrogen atom abstraction leading principally to glucopyran-2-ulosides. Fragmentation of the anomeric radical resulting in the formation of ring opened products is a problem in certain series. The chemistry is dictated to a considerable extent by the nature of the protecting groups employed with the 4,6-benzylidene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 107 publications
2
47
0
Order By: Relevance
“…Jarmila Brunckova thus prepared S-ethyl 4,6-benzylidene-a-Dthiomannopyranoside by standard means and converted it to the 3-O-benzyl-2-O-tertbutyldimethylsilyl derivative (14) by the aegis of dibutyltin oxide and benzyl bromide, then TBDMS triflate. [21] Brunckova noted the highly selective sulfoxidation process, which gave essentially a single diastereomer, in contrast to the unselective oxidations bthioglycosides observed previously, [23] but was unable to assign configuration at the time. [21] Brunckova noted the highly selective sulfoxidation process, which gave essentially a single diastereomer, in contrast to the unselective oxidations bthioglycosides observed previously, [23] but was unable to assign configuration at the time.…”
Section: Mannosyl Triflates From Mannosyl Sulfoxides and Thioglycosidmentioning
confidence: 85%
See 2 more Smart Citations
“…Jarmila Brunckova thus prepared S-ethyl 4,6-benzylidene-a-Dthiomannopyranoside by standard means and converted it to the 3-O-benzyl-2-O-tertbutyldimethylsilyl derivative (14) by the aegis of dibutyltin oxide and benzyl bromide, then TBDMS triflate. [21] Brunckova noted the highly selective sulfoxidation process, which gave essentially a single diastereomer, in contrast to the unselective oxidations bthioglycosides observed previously, [23] but was unable to assign configuration at the time. [21] Brunckova noted the highly selective sulfoxidation process, which gave essentially a single diastereomer, in contrast to the unselective oxidations bthioglycosides observed previously, [23] but was unable to assign configuration at the time.…”
Section: Mannosyl Triflates From Mannosyl Sulfoxides and Thioglycosidmentioning
confidence: 85%
“…In fact it was several years before Jan Mataka and Sanxing Sun were able to prepare crystalline derivatives suitable for X-ray analysis and so assign the configuration as S R . [21] The TBDMS protecting group was removed and was replaced by the radical precursor, and the radical inversion procedure was conducted with moderate success, comparable to that seen with the a-methyl mannoside. In line with our expectations, a good yield of a 10:1 mixture of glycosides (17) favoring the a anomer was obtained (Scheme 6).…”
Section: Mannosyl Triflates From Mannosyl Sulfoxides and Thioglycosidmentioning
confidence: 99%
See 1 more Smart Citation
“…While pursuing a radical‐based solution to the ubiquitous problem of stereoselective β‐mannopyranoside synthesis, Crich and co‐workers serendipitously uncovered an unappreciated level of complexity in Kahne's sulfoxide glycosylation method . When using benzylidene acetal protected donor 8 , Crich observed that the stereoselectivity of the reaction was dependent on the order of addition of the acceptor and activating agent (Scheme ).…”
Section: Stereoselective Synthesis Of β‐Mannopyranosides and α‐Glucopmentioning
confidence: 99%
“…Benzoylation of the b-d-mannopyranoside 47 gave mostly the 3-benzoate 48 [65], isolated in 90% yield ((S)-1) or 62.5% ((R)-1). Benzoylation of the a-d-mannopyranoside 49 was less strongly influenced by the catalysts than that of 27, providing 85, 62, and 74% of the 3-benzoate 51 [55] as the major product in the presence of (S)-1, (R)-1, and TMEDA, respectively.…”
Section: As Expected From the C(3)àoh ¥¥¥ Oàc(4) H-bond [52] In Methymentioning
confidence: 99%